Career Orientation Of Employees In Islamic Banks: Kingdom of Bahrain - Moovala, Vijayalaxmi (European Scientific Journal, ESJ, 2016)
The main aim of the study was to identify the career anchors of employees working in Islamic banks of Bahrain and to examine the similarities or differences, in the career anchor preferences of males and females, managers and non-managers, and among the three generations [baby-boomers, Gen X and Gen Y]. Edgar Schein’s eight career anchors formed the basis of this study. The study revealed that there is no significant difference in the career anchor preferences of the male, female, managers and non-managers. The main anchor for majority of these categories was technical/functional competence, for the second majority of respondents it was general managerial competence. The career anchors preference of babyboomers and Gen X, and Gen X and Gen Y was somewhat similar. However there was a variation in the career anchor preferences of baby-boomers and Gen Y. Majority of the baby-boomers and Gen X preferred technical/functional competence as their main anchor, and Gen Y opted for general managerial competence. The preferred anchor for the second majority of baby-boomers was security/stability, for Gen X general managerial competence and Gen Y pure challenge. The findings of this study would facilitate Islamic banks in Bahrain to develop appropriate career development plans based on their employee preferences. For male, female, managers and non-managers, career plans based on career anchors like technical/functional competence, and general managerial competence need to be made. Whereas for baby-boomers, Gen X and Gen Y relevant career plans based on specific preferences need to be formulated.